Linguocultural and didactic aspects of tourism discourse: issues in translation, cultural mediation, and teaching language for specific purposes (LSP) - Mustofokulov , Farkhod Kholmurod ugli (The Lingua Spectrum, 2026)
Tourism discourse represents a specialized communicative system designed to promote destinations, persuade potential travelers, and construct symbolic representations of places. This article investigates the linguistic, cultural, translational, and pedagogical dimensions of tourism discourse within the framework of Language for Specific Purposes (LSP). Drawing on corpus-based studies, discourse analysis, and linguodidactic research, the study explores how tourism texts function as tools of cultural mediation and how they can be effectively integrated into language teaching. The analysis demonstrates that tourism discourse combines persuasive language, multimodal communication, and culturally embedded meanings that require careful translation strategies. Findings also highlight the pedagogical value of authentic tourism materials such as travel blogs, promotional websites, and tourist guides in developing students’ intercultural competence and professional communication skills. The study concludes that tourism discourse is not merely promotional language but a complex intercultural communicative practice requiring specialized translation training and innovative didactic approaches.